Differential grain filling in apical and basal spikelets of compact panicle rice is associated with difference in expression of miRNAs targeting gene products involved in grain filling - Chandra, T; Shaw, B P (ORYZA-An International Journal of Rice, 2020)
Development of rice cultivars bearing numerous spikelets by breeding approach to increase production of the crop to feed the ever increasing human population accompanies poor filling of grains in their basal spikelets preventing achievement of the yield potential. To understand the reason of such poor grain filling at the level of the initial biochemical events, 5 RACE library was prepared taking RNA extracted from the spikelets of two indica rice cultivars, a compact-panicle Mahalaxmi bearing numerous spikelets per panicle (>350) and a laxpanicle Upahar bearing fewer spikelets (<250) per panicle, and the presence of the miRNA cleaved gene products involved in grain filling was identified by running PCR using gene-specific primers. Bioinformatics analysis was conducted to find if the grain filling enzymes were targeted by miRNAs. The effort led to identification of three enzymes, namely granule bound starch synthase, invertase and sucrose phosphate synthase, the transcripts of which were targeted by the miRNAs osa-miR160a-5p, osa-miR166e-3p and osa-miR156b-5p, respectively. The expressions of the three miRNAs were confirmed by Northern in the apical and basal spikelets of the two cultivars. The expression analysis of the three miRNAs further revealed that these were expressed significantly more in the basal spikelets than in the apical ones of Mahalaxmi, but not of Upahar. Real time PCR of the target genes showed an opposite result, i.e., these were expressed significantly less in the basal spikelets than in the apical ones of Mahalaxmi, but mostly not of Upahar. The finding led to the conclusion that the grain filling in rice could be regulated at the level of miRNAs, and manipulation of their expression could be proved an important tool in improving grain filling in compact-panicle rice cultivars.